ASEAN on Malaysia on 31st August 2001: a study of online newspapers - Fuziah Kartini Hassan Basri; Arfah Yusof; Mohd Safar Hasim; Normah Mustafa (Universiti Kebangsaan Malaysian, 2002)
please refer fulltext